International survey of injury surveillance practices in competitive swimming. (September 2022) - Barry, Lorna; Lyons, Mark; McCreesh, Karen; Powell, Cormac; Comyns, Tom
Abstract: Objective: The purpose of this study was to identify the injury surveillance practices being used in competitive swimming environments. It explored the nature of the data collected, the injury definitions used and the perceived effectiveness of injury surveillance. Finally, this study also examined barriers to injury surveillance. Design: Online cross-sectional. Participants: Twenty-two responders working in competitive swimming. Outcome measures: Injury surveillance methods, data collected, perceived level of effectiveness and barriers associated with injury surveillance. Results: Fifteen responders participated in injury surveillance, with 13 responders using a recognised definition for injury. Ten responders did not use any sports injury classification system. Ten responders found injury surveillance to be very effective at identifying injury trends, while previous injury history and training load data were perceived to be most influential in preventing injury. Limited time, funding and compliance were common obstacles, while poor staff communication and engagement were barriers to the effective implementation of injury surveillance. Conclusions: The implementation of injury surveillance is related to the system objectives, competitive level of those under surveillance and the resources available. This implementation requires the balance of adhering to the principles outlined in prominent consensus statements and overcoming the barriers associated with implementing a system effectively. Highlights: Only about two-thirds (68%) of responders employed injury surveillance practices. Only 53% of responders analysed the injury surveillance data once collected. Poor communication/engagement amongst the MDT is a barrier to injury surveillance. The primary goal of injury surveillance was "a record for insurance purposes".